The chest radiograph in cystic fibrosis: a new scoring system compared with the Chrispin-Norman and Brasfield scores. Issue 9 (September 1994) - Conway, S P; Pond, M N; Bowler, I; Smith, D L; Simmonds, E J; Joanes, D N; Hambleton, G; Hiller, E J; Stableforth, D E; Weller, P
Abstract : BACKGROUND--Scoring systems for the chest radiograph in cystic fibrosis are used to compare patients and different treatment regimens, and to monitor respiratory disease in individual patients. The Northern chest radiograph score was designed to allow one person to assess the radiological features of lung involvement in cystic fibrosis in as simple, rapid and equally reproducible manner as the established Chrispin and Norman, and Brasfield scoring systems. METHODS--Forty five chest radiographs were scored by 10 physicians with a special interest in cystic fibrosis according to the Brasfield and Northern methods, and by five pairs of physicians according to the Chrispin-Norman criteria. Three individuals and two pairs rescored the radiographs after an interval of 3-5 months. The Northern score was performed with and without a lateral view, using the original posteroanterior radiograph. RESULTS--The Northern score showed a better agreement between observers for the ranking of the radiographs. It was equally well related to respiratory function tests, the Shwachman-Kulczycki score of overall clinical status, and in its discrimination between different radiographs as the other two scoring systems. The Northern score performed equally well with or without a lateral film. CONCLUSIONS--The Northern system fulfils the requirements of a chest radiograph score more successfully than the Chrispin-Norman or Brasfield systems, and does not require a lateral film.